Effects of long-term training specificity on maximal strength and power of the upper and lower extremities in athletes from different sports - Izquierdo, M.; Häkkinen, K.; Gonzalez-Badillo, J. J.; Ibanez, J.; Gorostiaga, E. M. (European Journal of Applied Physiology, 2002)
Maximal concentric one repetition maximum half-squat (1RMHS), bench-press (1RMBP), power-load curves during concentric actions with loads ranging from 30% to 100% of 1RMHS and 1RMBP were examined in 70 male subjects divided into five groups: weightlifters (WL, n=11), handball players (HP, n=19), amateur road cyclists (RC, n=18), middle-distance runners (MDR, n=10) and age-matched control subjects (C, n=12). The 1RMHS values in WL, HP and RC were 50%, 29% and 28% greater, respectively, (P<0.001-0.01) than those recorded for MDR and C. The half-squat average power outputs at all loads examined (from 30% to 100%) in WL and HP (P<0.001 at 45% and 60% with HP) were higher (P<0.05-0.001) than those in MDR, RC and C. Average power output at the load of 30% of 1RMHS in RC was higher (P<0.05) than that recorded in MDR and C. Maximal power output was produced at the load of 60% for HP, MDR and C, and at the load of 45% for WL and RC. The 1RMBP in WL was larger (P<0.05) than those recorded in HP, RC, MDR and C. In the bench press, average muscle power outputs in WL and HP were higher (P<0.05-0.001) than those in MDR, RC and C, and were maximized at a load of 30% of 1RM for WL and HP, and at 45% for RC, MDR and C. In addition, the velocities that elicited the maximal power in the lower extremities were lower (0.75 m·s-1) than those occurring in the upper extremities (1 m·s-1). The data suggest that the magnitude of the sport-related differences in strength and/or muscle power output may be explained in part by differences in muscle cross-sectional area, fibre type distribution and in the muscle mechanics of the upper and lower limbs as well as by training background.